The Mexican Dream, What Drives the Mexican Millennial to invest? - Gordillo-Kontio, Ulla (My University, 2015)
The Mexican dream is the equivalent of the American Dream for Mexico. This thesis explores what is the equivalent of the American Dream for young Mexican adults (25 to 35 year old Mexicans). The aim of the study is to develop an understanding of the core values of young Mexican adults. The study is made for a case company, Expertos Patrimoniales Wealth Management Advisors, who intend to sell financial management services to these young Mexican adults in the next 5 to 10 years. This study implements a cross-cultural consumer behavior framework by David Luna, in order to consider factors like culture, and value systems to uncover the Mexican Dream for young Mexican adults. In order to gather data for this study, key informants were interviewed in specific areas, such as culture, financial consumer behavior and Mexican culture among others. The results suggest that independence is a strong driver for the young Mexican adults, independence from their family, from the corporate hierarchy and men. These core drivers differ from the traditional culture values where hierarchy and a secure job, family which includes the extended family and women´s economic dependency on men have been strong. Images of the future are created in order to understand the young Mexican adults Mexican Dream in the next 5 to 10 years, in order to provide useful information for the case company for the development of products and services that this segment of the Mexican market might find interesting in the near future.